2012
DOI: 10.1371/journal.ppat.1002579
|View full text |Cite
|
Sign up to set email alerts
|

HMOX1 Gene Promoter Alleles and High HO-1 Levels Are Associated with Severe Malaria in Gambian Children

Abstract: Heme oxygenase 1 (HO-1) is an essential enzyme induced by heme and multiple stimuli associated with critical illness. In humans, polymorphisms in the HMOX1 gene promoter may influence the magnitude of HO-1 expression. In many diseases including murine malaria, HO-1 induction produces protective anti-inflammatory effects, but observations from patients suggest these may be limited to a narrow range of HO-1 induction, prompting us to investigate the role of HO-1 in malaria infection. In 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
90
4
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 101 publications
13
90
4
5
Order By: Relevance
“…15 Subjects for our study were enrolled into a health center-based case-control study that has been described elsewhere. 15 Subjects were clinically assessed by a research physician and stringently classified as children with uncomplicated (mild) malaria (N = 146; 63 females and 83 males) and severe malaria (N = 135; 60 females and 75 males) resident in a restricted periurban area. Mild malaria was defined as an episode of fever (temperature 37.5 C) within the last 48 hours and more than 5,000 parasites/μL detected by slide microscopy.…”
mentioning
confidence: 99%
“…15 Subjects for our study were enrolled into a health center-based case-control study that has been described elsewhere. 15 Subjects were clinically assessed by a research physician and stringently classified as children with uncomplicated (mild) malaria (N = 146; 63 females and 83 males) and severe malaria (N = 135; 60 females and 75 males) resident in a restricted periurban area. Mild malaria was defined as an episode of fever (temperature 37.5 C) within the last 48 hours and more than 5,000 parasites/μL detected by slide microscopy.…”
mentioning
confidence: 99%
“…While in the former study COHb might have been generally overestimated, there was a significant increase in COHb levels from healthy controls with moderately severe and severe malaria. While the smaller but significant increase in COHb in patients with moderately severe malaria might indeed reflect a protective effect from an adequate increase in HO-1 activity, further increases in COHb seem insufficient or harmful (46,53). Besides a possible harmful effect of HO-1 superactivation, induction of COHb leads to a decrease in blood oxygen-carrying capacity.…”
Section: Carbon Monoxidementioning
confidence: 98%
“…Studies from Myanmar, Angola, and Gambia have found an association between shorter (GT) n dinucleotide repeat polymorphisms in the Hmox-1 promoter region-correlated with higher expression of the gene and higher levels of HO-1 in peripheral blood-and the incidence of severe malaria (45)(46)(47). The authors of the Gambian study argued that while this observation may simply reflect an adequate but insufficient response, the higher induction of HO-1 in patients with shorter (GT) n repeat alleles indicates that levels of HO-1 above a certain threshold might directly participate in the disease pathogenesis (48).…”
Section: Carbon Monoxidementioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 polymorphism is associated with susceptibility to malaria [51][52][53]. A genetic predisposition to higher levels of HO-1 is associated with severe malaria in Gambian children [54]. Moreover, vitamin D deficiency increases the expression of the hepatic mRNA levels of HO-1 in obese rats [41].…”
Section: The Genomic Factors Associated With Vitamin D In Malariamentioning
confidence: 99%